Exploring The Impact Of Textbook On Speaking Proficiency In Business Communication - Arya Eka Saputra; Muhammad Romdony; Abdul Syahid (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
In the context of a globalized economy, strong communication abilities, particularly speaking skills in English, are vital for marketing professionals to effectively engage in international business. This study examines the development of an English for Specific Purposes (ESP) course aimed at enhancing speaking proficiency among marketing professionals. A thorough needs analysis was conducted through surveys and interviews with industry experts to pinpoint essential speaking competencies needed in marketing scenarios, such as presentations, negotiations, and client communications. The course structure combines theoretical aspects of business communication with practical exercises, including role-plays, simulations, and peer feedback, equipping learners with the skills necessary for effective verbal interaction. It also focuses on real-life applications to ensure that participants can readily apply their skills in their work environment. The course's effectiveness was assessed through pre- and post-course evaluations, which demonstrated marked improvements in participants' speaking abilities and self-confidence. This research highlights the significance of specialized language training for the professional growth of marketing experts and emphasizes the necessity for continued exploration in the ESP domain to adapt to the changing landscape of global business communication.